2022
DOI: 10.1093/ajcn/nqac286
|View full text |Cite
|
Sign up to set email alerts
|

A red wine intervention does not modify plasma trimethylamine N-oxide but is associated with broad shifts in the plasma metabolome and gut microbiota composition

Abstract: Background Gut microbiota profiles are closely related to cardiovascular diseases through mechanisms that include the reported deleterious effects of metabolites, such as trimethylamine N-oxide (TMAO), which have been studied as diagnostic and therapeutic targets. Moderate red wine (RW) consumption is reportedly cardioprotective, possibly by affecting the gut microbiota. Objective To investigate the effects of RW consumption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 60 publications
1
32
0
Order By: Relevance
“…Similar results in terms of increased faecal microbial diversity, have been obtained both in healthy individuals [81,99] and in patients with metabolic alterations associated with obesity [83]. Plasma trimethylamine N-oxide (TMAO) did not differ between people receiving the RW intervention and ET abstention [99].…”
Section: Gut Microbiota and Gastrointestinal Tractsupporting
confidence: 69%
See 2 more Smart Citations
“…Similar results in terms of increased faecal microbial diversity, have been obtained both in healthy individuals [81,99] and in patients with metabolic alterations associated with obesity [83]. Plasma trimethylamine N-oxide (TMAO) did not differ between people receiving the RW intervention and ET abstention [99].…”
Section: Gut Microbiota and Gastrointestinal Tractsupporting
confidence: 69%
“…Another study demonstrated that RW consumption induced a significant increase in amounts of Bifidobacterium and Prevotella with a negative correlation with lipopolysaccharide (LPS) plasma concentration [73]. Similar results in terms of increased faecal microbial diversity, have been obtained both in healthy individuals [81,99] and in patients with metabolic alterations associated with obesity [83]. Plasma trimethylamine N-oxide (TMAO) did not differ between people receiving the RW intervention and ET abstention [99].…”
Section: Gut Microbiota and Gastrointestinal Tractmentioning
confidence: 62%
See 1 more Smart Citation
“…Red wine consumption was significantly associated with an increase in the relative abundance of Bacteroides , Ruminococcaceae , Roseburia and Prevotella . Interestingly, Parasutterella was the most prominent genus for differentiating the gut microbiota of the participants who consumed red wine 52 . A previous study showed that Parasutterella supports interspecies metabolic interactions within the healthy gut ecosystem 53 .…”
Section: Methodsmentioning
confidence: 92%
“…Interestingly, Parasutterella was the most prominent genus for differentiating the gut microbiota of the participants who consumed red wine. 52 A previous study showed that Parasutterella supports interspecies metabolic interactions within the healthy gut ecosystem. 53 A recent review investigated the potential benefits of theaflavins, found in red wine, on metabolic syndrome, with a focus on the gut microbiome.…”
Section: Methodsmentioning
confidence: 98%